Adherence to the Mediterranean lifestyle in patients after myocardial infarction. (11th May 2021) - Novakovic, M; Tasic, J; Krevel, B; Rajkovic, U; Bozic Mijovski, M; Kosuta, D; Trsan, J; Fras, Z; Jug, B
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: ReKoBo study group INTRODUCTION: Adherence to the Mediterranean diet is associated with decreased cardiovascular and overall mortality, and is recommended by the relevant preventive cardiology guidelines. However, besides specific dietary intake, Mediterranean lifestyle includes a series of eating habits and social behaviours. All these aspects are summed in the Medlife questionnaire. PURPOSE: The aim of our study was to assess adherence to the Mediterranean lifestyle and examine associations with clinically relevant variables, in patients after myocardial infarction referred to cardiac rehabilitation. METHODS: This was a single-centre cross-sectional study. Mediterranean lifestyle pattern was assessed using a validated Medlife questionnaire, which includes 28 questions (15 questions on the Mediterranean diet adherence, 6 questions on the eating habits and behaviour, and 7 questions on the social pattern of the Mediterranean lifestyle). Associations of the Medlife score with the exercise performance (assessed by the cardiopulmonary exercise testing), clinical data, demographics, lipid status, and quality of life (assessed by the HeartQol questionnaire) were assessed using Spearman's correlation coefficient, while differences between two groups were determined with the independent-samples t-test. RESULTS: There were 111 patients included in the study, mean age 55 +/- 10 years, 20% of them were women. Adherence to the Mediterranean lifestyle was not associated with age, BMI, peak VO2, total or LDL cholesterol. Also, there were no differences in terms of Medlife score between women vs. men, and between patients living in urban vs. rural areas. There were, however, significant associations between Medlife score and HDL (r = 0.239, p = 0.012), triglyceride level (r=-0.383, p < 0.001) and blood glucose level (r=-0.214, p = 0.024), and with the emotional aspects of the quality of life (r = 0.245, p = 0.017). Also, higher-educated were significantly more adherent to the Mediterranean lifestyle as compared to lower-educated patients (16.2 vs. 14.7 points, p = 0.018). CONCLUSION: Poorer adherence to the Mediterranean lifestyle is associated with substandard control of lipid status and glucose level. Improvement in the Mediterranean lifestyle adherence might be a cornerstone in the cardiac rehabilitation beyond exercise training programmes.